Introduction of energy-saving technologies to improve the effectiveness of food enterprises functioning - I. V. Balashova; T. A. Tereshchenko (Новые технологии)
In the article possibilities of introduction of resource-saving technologies are considered, necessity of use of energy-resource-saving measures to increase the efficiency of domestic food enterprises functioning is proved.